A biobank of patient-derived pediatric brain tumor models - Brabetz, Sebastian; Korshunov, Andrey; Balasubramanian, Gnana Prakash; Chavez, Lukas; Jones, David T. W.; Pfister, Stefan; Kool, Marcel (Nature medicine, 2018)
A resource of preclinical pediatric brain tumor models with detailed molecular characterization provides a platform for the community to test novel therapeutic approaches.